2017
DOI: 10.1126/sciadv.1701483
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced twisting of nanoplatelets and their self-assembly into chiral ribbons

Abstract: Organic ligands can induce twist on nanometer-thin crystalline platelets and on their self-assembled ribbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(157 citation statements)
references
References 44 publications
(53 reference statements)
6
145
0
Order By: Relevance
“…For example, the evaporation‐induced self‐assembly of Ag nanoprisms into 2–3 µm long helical columnar structures has been reported (Figure C), which was attributed to the strong binding thiol chiral ligand . Similarly, it has been demonstrated that chiral molecules can induce the twisting of CdSe nanoscale platelets into chiral ribbons with a pitch of ≈ 400 nm . In a very different manner, the illumination of racemic CdTe NPs with right‐ or left‐handed circularly polarized light (CPL) induced the assembly of right‐ or left‐handed twisted ribbons, with total lengths of 3 ± 0.5 µm and pitch lengths of 800 ± 20 nm .…”
Section: The Chiroptical Effects For Different Nanostructuresmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, the evaporation‐induced self‐assembly of Ag nanoprisms into 2–3 µm long helical columnar structures has been reported (Figure C), which was attributed to the strong binding thiol chiral ligand . Similarly, it has been demonstrated that chiral molecules can induce the twisting of CdSe nanoscale platelets into chiral ribbons with a pitch of ≈ 400 nm . In a very different manner, the illumination of racemic CdTe NPs with right‐ or left‐handed circularly polarized light (CPL) induced the assembly of right‐ or left‐handed twisted ribbons, with total lengths of 3 ± 0.5 µm and pitch lengths of 800 ± 20 nm .…”
Section: The Chiroptical Effects For Different Nanostructuresmentioning
confidence: 98%
“…. The chiral architectures (NP dimers, pyramids, and helices) so far reported have involved DNA, proteins, peptides, fibers, supermolecules, inorganic pores, and template‐free (interparticle forces, evaporation, or light,) assemblies.…”
Section: Introductionmentioning
confidence: 99%
“…Ligand surface coverage can greatly influence the structures of 2D SNMs . Abécassis et al found that the prepared stacked CdSe nanoplate superstructure would spontaneously twist upon the addition of oleic acid ligands, resulting in chiral ribbon superstructures several micrometers in length . The increasing surface strain induced by the ligand accounted for the morphological transition.…”
Section: Ligand Effects On Snmsmentioning
confidence: 99%
“…Meanwhile, the flexibility might also be influenced by the surface ligand. In addition, ligand can also influence the behavior in the process of catalysis, self‐assembling, optics, etc., and it has been revealed that both the ligand type and ligand coverage play essential roles in properties. These features have seldom been observed in the materials with larger sizes.…”
Section: Introductionmentioning
confidence: 99%
“…These chiral molecules and their mirror images (enantiomers) exhibit opposite handedness when interacting with circularly polarized light, as well as different chemical and biological performance. Inspired by chiral molecular structures, researchers are developing strategies to build artificial chiral materials by mimicking molecular structures using functional materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Specifically, metal nanomaterials exhibit tailorable optical properties upon excitation of surface plasmons and become one of the most promising components to realize of chiral optical metamaterials [15,16].…”
Section: Introductionmentioning
confidence: 99%